Analisis Konten Penilaian Pengungkapan Keselamatan Kerja pada Laporan Keberlanjutan Perusahaan Tambang - Pratama, Kelvin; Siregar, Anitaria (Fakultas Ekonomi Universitas Gresik, 2023)
Implementing occupational health and safety in the work area is a form of respect for human rights. Therefore, this research wants to examine the implementation of occupation health and safety in the field to examine whether it only refers to the constitutional law or surpasses the constitutional law. The researcher uses the scoring analytics method by giving a score of 0 if the company does not reveal the Occupational health and safety issues, giving a score of 1 if the disclosure only follows the measurement and a score of 2 if the exposure is beyond the criterion or the rules. The indicator is arranged based on the Decree of the Director-General of Coal Minerals of the Ministry of Energy and Mineral Resources Number 185.K/37.04/DJB/2019. Based on the research result, the implementation of Occupational health and safety in most companies only refers to the constitutional law. The disclosure that can make the revelation surpass the indicator is about the control of Covid-19 spread and international certification for the implementation of Occupational health and safety. Other factors that can impact occupational health and safety disclosure are the parent company's location, the existence of a foreign commissioner, and the type of company ownership.